(untitled) (Nepal Agriculture Research Journal, 2014)
Bacterial wilt caused by Ralstonia solanacearum E.F. Smith is one of the destructive diseases of tomato. Experiments were conducted to confirm the resistance and to evaluate varieties received from Asian Vegetable Research and Development Center against bacterial wilt disease in the farmers’ bacterial wilt sick fields at Thaiba and at Panchkhal during 1999 and 2000-2001 respectively. A total of five varieties such as CLN 2026 C, CLN 2026 D, CLN 1466 J, CLN 1466 P and susceptible check Lapsigede or L 390 were included in the experiments. Randomized complete block design with 4 replications was commenced at both the locations. In terms of disease incidence and yield parameters as well as consumers’ preference on the fruit size, CLN 2026 C was found the best variety followed by CLN 2026 D. Wilt incidence was significantly lower in those varieties showing resistant reaction than in susceptible check. However, the marketable fruit yields were significantly higher with low wilt incidences in CLN 1466 P and CLN 1466 J also compared to susceptible check. But the large fruit size of those varieties was not acceptable to the consumers and the growers. Thus, CLN 2026 C and CLN 2026 D could be used as resistant variety to minimize crop losses from bacterial wilt disease. Nepal Agric. Res. J. Vol. 8, 2007, pp. 50-55 DOI: http://dx.doi.org/10.3126/narj.v8i0.11580